Postactivation potentiation effect of two lower body resistance exercises on repeated jump performance measures - Gahreman, Daniel; Moghadam, Mehdi; Hoseininejad, Ehsan; Dehnou, Vahid; Connor, Jonathan; Doma, Kenji; Stone, Michael (Biology of Sport, 2020)
This study examined the postactivation potentiation effects of combining squat and deadlift exercises on subsequent repeated jump performance. Fifteen, resistance-trained youth wrestlers were randomly allocated to either undertake back squats (BSq), deadlift (DL) or BSq and DL as supersets (BSq+DL), with a repeated jump protocol performed 8-minutes post-exercise in each session. Thereafter, a control condition (CON) was completed involving a general warm-up, followed by the repeated jump protocols. Power outputs, flight time, contact time and reactive strength index were recorded from each repeated jump protocol. Measures were compared between the BSq, DL and BSq+DL sessions and between sessions that generated the best power output (BEST) with CON via inferential statistics and effect size (ES) calculations. The BSq condition exhibited significantly greater power output compared to the CON condition (p<0.05, ES = 1.07), although no differences were identified for the other conditioning activities. Furthermore, power output, flight time and reactive strength index were significantly greater for the BEST compared to the CON condition (p<0.05, ES = 0.97–1.47). Results indicated that BSq was the optimal conditioning activity to increase power output during a repeated jump protocol. However, greater improvement during the BEST condition suggests that the type of conditioning activity should also be considered on an individual-basis.